1995
DOI: 10.1162/pres.1995.4.1.64
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Measure of Telepresence

Abstract: This paper presents the foundation for a theory of presence that seeks to answer important questions about telepresence and virtual presence. The theory, which develops the definition of telepresence to include virtual presence as a special case, permits the precise definition of various types and degrees of telepresence. General categories of telepresence are defined, using different types of presence that are proposed in the paper. Three types of specifications are used to make the definitions more precise: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(76 citation statements)
references
References 1 publication
2
73
0
1
Order By: Relevance
“…This vision describes presence as "Media Presence", a function of our experience of a given medium [7][8][9][10]. The main outcome of this approach is the "perceptual illusion of nonmediation" [10] definition of presence.…”
Section: Virtual Reality: From Technology To Experiencementioning
confidence: 99%
“…This vision describes presence as "Media Presence", a function of our experience of a given medium [7][8][9][10]. The main outcome of this approach is the "perceptual illusion of nonmediation" [10] definition of presence.…”
Section: Virtual Reality: From Technology To Experiencementioning
confidence: 99%
“…Hendrix and Barfield (1996a, 1995, however, have found that differently worded questions produced similar results, thus providing some evidence that this latter case may not be a major problem.…”
Section: Yesmentioning
confidence: 92%
“…As we can see clearly, almost all the definitions above correspond to the sense of presence induced by mediation (from the perspective of virtual reality and computer mediated environments). Presently this sense of presence that we experience (different from physical reality) is being studied from various disciplines associated with cognitive science (for instance, film theory and art, television and media [15], literature theory [16], teleoperation [3,17], communication media [1], video games and serious games [18,19], virtual reality [5,13,20].…”
Section: The Sense Of Presencementioning
confidence: 99%
“…They illustrated how the phenomenon of self-projection relies on a personal mental simulation of another time, place or perspective. This attribute is comparable to one of the primary characteristics of a virtual reality illusion that gives us the feeling of 'telepresence' [3,17] or a sense of 'transportation' to a virtual world [16] or what Rheingold [20] called 'a form of out-of-body experience'.…”
Section: Similarities With Presence In Virtual Reality (Or Media-evokmentioning
confidence: 99%